Noise source identification of engine dynamometer - Ab Rahman, Mohd Nooh (2008)
This project presents the effort taken to determine the major source of the noise and verify the frequency resonance and amplitudes for different engine speed of the engine dynamometer in automotive research laboratory of Universiti Malaysia Pahang (UMP).The research describes the experimental set-up and investigation of the mechanisms of engine dynamometer noise generation and the corresponding countermeasures employed during the engine performance tested. According to the analysis of acoustic signals and vibration signals measurement, an investigation of the noise source identification in a diesel engine is presented, and that the noise level of the diesel is comprehended. The experiment carried out with several altered parameters for flexibility investigation. With the sound intensity method, the results of the noise source of flywheel cover and exhaust were presented. The results of analysis showed that the 1250 Hz bands had the most significant contribution to the engine right noise. For the 1500rpm, 2000rpm and 2500rpm the sound power level are 86.42dB, 92.44 and 96.34dB respectively. These clearly show that higher rpm will increase the noise at the engine. Additionally mounting area noise for this engine also give significant effect with the value of 77.71dB for 1500rpm and 89.86db for 2500rpm due to the engine’s structural vibration transfer and noise radiation behavior with respect to the excitation mechanism. The research also provides the reliable basis for the engineering practice to reduce noise level.